Not only tourism: unravelling suburbanization, second-home expansion and "rural" sprawl in Catalonia, Spain. Issue 1 (2nd January 2017) - Cuadrado-Ciuraneta, Sergi; Durà-Guimerà, Antoni; Salvati, Luca
ABSTRACT: This study illustrates multifaceted urbanization patterns and processes in a coastal region of Catalonia (northeastern Spain) as a paradigmatic example of the socio-economic transformations typically observed in the northern Mediterranean basin since World War II. By focusing on the expanding tourism industry, second-home expansion, infrastructural development and sprawl around traditional rural centres, the paper assesses the effects of long-term economic, demographic, social and cultural transformations on rural landscapes in Alt Empordà, the so-called "Catalan Tuscany". The stratification of distinct urbanization waves and the underlying socio-economic processes observed in Alt Empordà reflect population dynamics and settlement morphologies typical of rural districts moving rapidly towards a suburban spatial organization. Recent urban dynamics in Mediterranean rural systems deserve further investigation in order to shed light on latent suburbanization processes involving marginal European regions.